An integral assessment of landslide dams generated by the occurrence of rainfall-induced landslide and debris flow hazard chain - Ortiz-Giraldo, Laura; Botero, Blanca A.; Vega, Johnny (Frontiers in Earth Science, 2023)
Landslides caused by rainfall are one of the most frequent causes of disasters in tropical countries and mountainous terrain and can block rivers generating landslide dams. This paper presents a methodology for the estimation of the obstruction of water streams generated by rainfall-induced shallow landslides. The spatial distribution of the landslide hazard was estimated in terms of the Factor of Safety (FoS) values using the deterministic method with physical basis SLIDE (Slope - Infiltration - Distributed Equilibrium). The rainfall regimes of the study area were estimated by means of a simple scaling Log Normal Model. Subsequently, the resulting areas with a high hazard level that could detach and reach the riverbed were identified as sources for the simulation of the debris flow runout using the Rapid Mass Movement Simulation model with its debris flow module, (i.e., RAMMS-DF), estimating zones of the riverbed that should be analyzed in detail. Finally, the effects of river channel obstructions generated after debris flow movement were analyzed by means of the Iber, a well-known, physically based 2D hydraulic model and their possible changes on the river hydraulic. In order to generate a workflow that allows the application of the SLIDE methodology and the preparation of inputs for the subsequent processes of debris flow propagation and hydraulic modeling of the river corridor of analysis, a Python-based toolbox was created. Our results highlight the changes in the fluvial dynamics in the corridor of the river of analysis after the landslide dams generated by the occurrence of rainfall-induced landslide and debris flow hazard chain for the different return periods. In all cases, the material deposited in the river channel was sufficient to change the hydraulic regime of the river corridor, showing longer delay times in the transit of the flow, in addition to the decrease in the specific flow. This would imply a water shortage in the study basin of the hydroelectric project; however, in the scope of this project it is not possible to really determine the real effects that could be generated by this event.